HUBUNGAN ANGGARAN PARTISIPASI DAN BUDGETARY SLACK DENGAN INTERNAL CONTROL SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS DI PTS KABUPATEN JOMBANG) - Rachma Agustina; Sri Trisnaningsih (BAJ: Behavioral Accounting Journal, 2019)
This study aims to determine the direct effect of budgetary participation on budgetary slack; the effect of the interaction between internal control and budgetary participation on budgetary slack. This type of quantitative research with purposive sampling method. The study population was 204 managers from 9 PTS, while a sample of 51 from 6 PTS in Jombang. Data analysis techniques with the SPSS program use data quality tests, classic assumption tests and hypothesis testing in the form of Moderated Regression Analysis (MRA). The results showed that budgetary participation did not affect budgetary slack directly, the interaction of internal control with budgetary participation did not affect budgetary slack.